ChemInform Abstract: Selected Organophosphorus Compounds with Biological Activity. Applications in Medicine. Issue 12 (March 2016) - Demkowicz, Sebastian; Rachon, Janusz; Dasko, Mateusz; Kozak, Witold
Abstract: Review: 121 refs.